Diet Quality Scores Are Positively Associated with Whole Blood–Derived Mitochondrial DNA Copy Number in the Framingham Heart Study. Issue 3 (7th December 2021) - Ma, Jiantao; Liu, Xue; Zhang, Yuankai; Cheng, Hanning; Gao, Wencheng; Lai, Chao-Qiang; Gabriel, Stacey; Gupta, Namrata; Vasan, Ramachandran S; Levy, Daniel; Liu, Chunyu
ABSTRACT: Background: The association between diet quality and mitochondrial DNA copy number (mtDNA-CN) remains to be examined. Objectives: We aimed to study the relation between diet quality and mtDNA-CN. Methods: We analyzed data from 2931 Framingham Heart Study (FHS) participants (mean age of 57 y, 55% females). Whole-genome sequencing was used to calculate mtDNA-CN from whole-blood samples. We examined the cross-sectional associations between 3 diet quality scores, the Dietary Approaches to Stop Hypertension (DASH) score, the Alternative Healthy Eating Index (AHEI), and the Mediterranean diet score (MDS), and mtDNA-CN. Linear mixed models were used to account for maternal lineage. Results: We observed that a higher DASH score was positively associated with mtDNA-CN after adjusting for sex, age, energy intake, smoking status, alcohol intake, and physical activity level. A 1-SD increase in the DASH score was associated with a 0.042-SD greater mtDNA-CN (95% CI: 0.007, 0.077; P = 0.02). Similarly, for each SD increase in AHEI and MDS, the mtDNA-CN SD increased by 0.056 (95% CI: 0.019, 0.092; P = 0.003) and 0.047 (95% CI: 0.01, 0.083; P = 0.01), respectively. Diet quality scores were associated with neutrophil and lymphocyte counts but not platelet counts, e.g., for a 1-SD increase in the DASH, neutrophils decreased by 0.8% (95% CI: 0.5%, 1.1%; P = 4.1 × 10 –6 ), lymphocytes increased by 0.7% (95% CI: 0.4%, 1%, P = 1.2 × 10 –5 ), and there was no significant change in platelet number (0.1 × 1000/μL; 95% CI: –1.6, 1.9; P = 0.89). Further adjustment for neutrophil, lymphocyte, and platelet counts and the associations between diet quality scores and mtDNA-CN were completely attenuated to nonsignificant ( P = 0.95, 0.54, and 0.91, respectively). Conclusions: We observed that higher diet quality is associated with a greater whole-blood derived mtDNA-CN in middle-aged to older adult FHS participants, and that blood cell composition, particularly neutrophil counts, attenuated the association between diet quality and mtDNA-CN.